Experimental study of 4n with 8He(p, 2p) reaction. (December 2020) - Huang, S. W.; Yang, H.; Marqués, F. M.; Achouri, N. L.; Ahn, D.S.; Aumann, T.; Baba, H.; Beaumel, D.; Böhmer, M.; Boretzky, K.; Caamaño, M.; Chen, S.; et al.
Abstract: The tetraneutron has attracted the attention of nuclear physicists during the past decades, but there is still no unambiguous confirmation of its existence or non-existence. A new experiment based on 8 He( p, 2p ) 7 H{ t + 4 n } reaction, with direct detection of the four neutrons, has been carried out at RIBF, which can hopefully help to draw a definite conclusion on the tetraneutron system.